Comparison of The Antiglycation Effect of Pyridoxamine and Nettle Hydroalcoholic Extract on Albumin - Al-Silaykhee, Mohammed Abbas (Medical Science Journal for Advance Research, 2024)
Background: Free radicals are highly reactive molecules that cause oxidative damage to fats, proteins, and nucleic acids. Therefore, they play a crucial role in the development of many diseases such as heart disease, cancer, and abnormal brain function. The human body is equipped with antioxidants that neutralize free radicals, preventing their accumulation in tissues. The imbalance between the production of these radicals and the level of antioxidants leads to oxidative stress, where an increase in free radical production reduces antioxidant levels, causing a deficiency in the body. On the other hand, evidence indicates that oxidative stress contributes to the onset and exacerbation of diabetes-related complications and plays a significant role in non-enzymatic glycation of proteins (Riahi et al., 2014). Therefore, any diabetes treatment must directly or indirectly reduce non-enzymatic protein glycation and oxidative stress. Non-enzymatic protein glycation and the formation of AGEs are factors involved in the pathogenesis of chronic diabetes complications. Since glycation reactions are accompanied by oxidation reactions, leading to the improper function of proteins, plant-derived antioxidant compounds can be used as a therapeutic approach to prevent the onset of these chronic complications.